Balancing expenditures on mitigation of and adaptation to climate change : an exploration of Issues relevant to developing countries - Shalizi, Zmarak 1947- (The World Bank, 2007)
Although climate policies have been so far mostly focused on mitigation, adaptation to climate change is a growing concern in developed and developing countries. This paper discusses how adaptation fits into the global climate strategy, at the global and national levels. To do so, a partial equilibrium optimization model of climate policies-which includes mitigation, proactive adaptation (ex ante), and reactive adaptation (ex post)-is solved without and with uncertainty. Mitigation, proactive adaptation, and reactive adaptation are found to be generally jointly determined. Uncertainty on the location of damages reduces the benefits of "targeted" proactive adaptation with regard to mitigation and reactive adaptation. However, no single country controls global mitigation policies, and budget constraints might make it difficult for developing countries to finance reactive adaptation, especially if climate shocks affect the fiscal base. Rainy-day funds are identified as a supplemental instrument that can alleviate future budget constraints while avoiding the risk of misallocating resources when the location of damages is uncertain